Indications Of Monopolistic Practices In The Single Digital Payment Method For Purchasing Train Tickets PT. KAI - Yuliana Yuliana (Fakultas Hukum Dehasen, 2024)
PT KAI cooperates with one of the state-owned financial technology companies, Link Aja. The cooperation is implemented with PT KAI's policy that requires the purchase of local or long-distance train tickets can only be done by using the KAI Access application. Payment methods with digital wallets available in the KAI Access application can only be with the Link Aja payment method. In fact, there are various digital wallets that are used besides Link Aja. From these problems, this research was compiled. The research aims to analyze the suitability of the functions and roles of SOEs in the implementation of financial services companies. In addition, it also aims to analyze the supervisory function of SOEs in preventing monopolistic practices in carrying out their business and what are the legal consequences for SOEs that are proven to have committed monopolistic practices. This research is included in the type of normative legal research with a statutory approach and conceptual approach. The results show that the cooperation between PT KAI and Link Aja in KAI Access digital payments is in accordance with applicable regulations and the role of SOEs to support economic growth and financial inclusion.